Putative multiple myeloma susceptibility genes identified by exome sequencing of 347 familial and early-onset cases - Pertesi, Maroulio; Demangel, Delphine; Niroula, Abhishek; Perrial, Emeline; Mahecha Escobar, Maria Laura; Vallée, Maxime; Liacos, Christine; Samur, Mehmet K; Sperling, Adam S; Munshi, Nikhil C; Kastritis, Efstathios; Dimopoulos, Meletios A; et al. (Leukemia, 2025)
Multiple myeloma (MM) is the second most common blood malignancy, with several lines of evidence supporting an inherited genetic component. Here, we sequenced 177 affected individuals from 128 families, and 170 early-onset MM cases diagnosed before 55 years of age. Samples were identified and collected through nationwide efforts in France, Sweden, and Greece. We focused on rare germline protein truncating and likely deleterious missense variants in genes harboring variants in at least two families showing variant-disease segregation, and in additional index (≥2) and/or early-onset (≥2) cases. We identified likely pathogenic variants in ATM (N = 12), ANGPTL6 (N = 5), and FBXW9 (N = 6). Additionally, we detected variants in previously reported MM predisposition genes, including DIS3, EP300, and KDM1A. Our results represent the largest sequencing study on familial and early-onset MM to date, and further illuminate the constitutional genetic basis of MM.
© 2025. The Author(s), under exclusive licence to Springer Nature Limited.